Pelatihan Desain Pembelajaran Ekonomi Berbasis 4C Bagi Guru Sekolah Menengah Atas di Kota Payakumbuh - Marna, Jean Elikal; Hayati, Annur Fitri (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
Responding to the latest policy set by the Minister of Education and Culture related to the preparation of Learning plans which must include 4C skills in learning activities, however, the readiness and skills of teachers in designing lessons that contain these 4C skills, from planning, implementation and evaluation are still lacking. Based on these problems, it is important for teachers to get training related to the 4C skills, in order to form a generation that has competencies that are able to compete in the future, therefore the community service team carries out community service activities with the methods or approaches used in community service. this community is training with integrated guidance consisting of offline activities, online activities and assignment activities. This activity was attended by 20 Economics teachers in Payakumbuh City which was equivalent to 32 hours of training in 3 months of implementation. This community service activity was carried out well with increasing teacher competence in designing economic learning plans based on 4C learning skills